2017
DOI: 10.1111/bph.13946
|View full text |Cite
|
Sign up to set email alerts
|

Diminazene aceturate prevents nephropathy by increasing glomerular ACE2 and AT2 receptor expression in a rat model of type1 diabetes

Abstract: DIZE treatment reduced diabetes-induced renal damage as shown by reduction of fibrosis and apoptosis. These protective actions of DIZE were blocked by the AT receptor antagonist. Taken together, these results suggest that DIZE protected against DN through the ACE2/angiotensin-(1-7)/ AT receptor axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 54 publications
3
45
2
Order By: Relevance
“…All other mice received equivalent volumes of vehicle (saline) injections. This dose was based on several previous studies showing that the optimal dose of DIZE in inducing ACE2 activity was 15 mg/kg/ day [39,43,44] and a preliminary study of our own across a range of DIZE concentrations by IP that confirmed previous findings (data not shown).…”
Section: Drugssupporting
confidence: 69%
“…All other mice received equivalent volumes of vehicle (saline) injections. This dose was based on several previous studies showing that the optimal dose of DIZE in inducing ACE2 activity was 15 mg/kg/ day [39,43,44] and a preliminary study of our own across a range of DIZE concentrations by IP that confirmed previous findings (data not shown).…”
Section: Drugssupporting
confidence: 69%
“…Wild-type mice were randomly divided into five groups (n = 10 each) as follows: 1) wild-type control group, 2) wild-type silicosis model group, 3) DIZE (15 mg/kg/day, i. p., D7770; Sigma-Aldrich, St. Louis, MO, USA) 15 treatment group, 4) DIZE + A779 (5 mg/kg/day, s.c., 4030357; Bachem, Bubendorf, Switzerland) 16 treatment group, and 5) DIZE + MLN-4760 (1 mg/kg/day, s.c. 530,616; Millipore, Darmstadt, Germany) 17 treatment group. The hACE2-transgenic ICR mice were randomly divided into four groups (n = 10 each) as follows: 1) hACE2-transgenic control group; 2) hACE2-transgenic silicosis model group, 3) A779 treatment group, and 4) MLN-4760 treatment group.…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%
“…Interestingly, diabetic rats using streptozotocin, treatment with DIZE restored ACE2 expression in isolated glomeruli and this was associated with increased expression of AT2R . DIZE reduced AngII levels in the whole kidney of diabetic rats and augmented Ang (1‐7) expression . The AT2R antagonist, PD123319 reversed the effect of DIZE, suggesting that DIZE protects the kidney via the ACE2/Ang (1‐7)/AT2 pathway …”
Section: The Potential Role Of Dize In Treating Vascular/endothelial mentioning
confidence: 98%
“…46 Interestingly, diabetic rats using streptozotocin, treatment with DIZE restored ACE2 expression in isolated glomeruli and this was associated with increased expression of AT2R. 49…”
Section: Dize In Cardiac and Renal Tissuementioning
confidence: 98%
See 1 more Smart Citation